Analisis Keuntungan Usaha Budidaya Spirulina di PT Munda Green Energy - Azhar, Mohamad Farid; Puspitaningrum, Dwi Aulia (Universitas Galuh, 2024)
The aimed of the research were: 1) to analyze the procedures for cultivating Spirulina at PT Munda Green Energy, 2) to analyze the role of factors production in Spirulina cultivation at PT Munda Green Energy, and 3) to analyze the profit of the Spirulina cultivation business at PT Munda Green Energy. The type of research used in this research was quantitative research with descriptive analysis and a case study approach method. The types of data used in this research were primary and secondary data. The data collection methods used in this research include observation, interviews, and documentation. The data analysis techniques used in this research were descriptive analysis techniques and analysis of farming. The results of the research showed that: 1) Spirulina cultivation procedures at PT Munda Green Energy include preparing planting media, spreading and transferring seeds, fertilizing and providing additional minerals, plant care, harvesting and drying, 2) seed production factors, fertilizer, water, labor, and temperature play an important role in Spirulina cultivation at PT Munda Green Energy, and 3) the revenue was received by PT Munda Green Energy from Oktober until December 2023rd was IDR 59.850.000/production with explicit costs of IDR 29.665.578,75/production and implicit costs of IDR 22.699.910/production resulting in a profit amounting to IDR 7.484.511,25/production.